Comparison of anaphylaxis epidemiology between urban and suburban pediatric emergency departments - Dhritiman Gurkha; Robert Podolsky; Usha Sethuraman; Kelly Levasseur (BMC, 2023)
Abstract Background Anaphylaxis is a serious allergic reaction that is rapid in onset and may cause death. To date, there are no published data on epidemiology of pediatric anaphylaxis in Michigan. Our objective was to describe and compare the time trends in incidence of anaphylaxis in urban and suburban populations of Metro Detroit. Methods We performed a retrospective study of Pediatric Emergency Department (ED) anaphylaxis visits from January 1, 2010, to December 1, 2017. The study was conducted at 1 suburban ED (SED) and 1 urban ED (UED). We identified cases using an International Classification of Diseases (ICD) 9 and 10 query of the electronic medical record. Patients were included if they aged 0-17 years and met the 2006 National Institute of Allergy and Infectious Disease and the Food Allergy and Anaphylaxis Network diagnostic criteria for anaphylaxis. The anaphylaxis rate was calculated as the number of detected cases divided by the total number of pediatric emergency room visits for that month. Anaphylaxis rates were compared between the two EDs using Poisson regression. Results A total of 8,627 patient encounters had ICD codes for anaphylaxis, of which 703 visits fulfilled the inclusion criteria and were used in subsequent analyses. Overall, the incidence of anaphylaxis was more common in males and in children < 4 years of age in both centers. Although the total number of anaphylaxis related visits was higher at UED over the eight-year time frame for this study, the anaphylaxis rate (cases per 100,000 ED visits) throughout the study was higher at the SED. While the observed anaphylaxis rate at UED was 10.47 - 162.05 cases per 100,000 ED visits, the observed anaphylaxis rate at SED was 0 - 556.24 cases per 100,000 ED visits. Conclusion Pediatric anaphylaxis rates differ significantly between urban and suburban populations in metro Detroit EDs. The rate of anaphylaxis related visits to the ED has significantly increased over the past 8 years in the metro Detroit area, with significantly higher rise in suburban compared to urban ED. More studies are needed to explore the reasons for this observed difference in increase rates.